PROFIL MOTIVASI BELAJAR SISWA WITHDRAWAL SMPN 1 SUCINARAJA - Anne Nurbaeti; Wikanengsih Wikanengsih; Tita Rosita (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
The purpose of this study was to determine the profile of students' motivation withdrawal at SMPN 1 Sucinaraja. Students withdraw or break away are students who show escape, both attention or interest in the social environment. The sampling technique in this study used a nonprobability sampling technique with a sample of 51 students. Researchers interested of SMPN 1 Sucinaraja. Based on the results of the study It is expected that students' motivation in SMPN 1 Sucinaraja is in the medium category with the distribution of students 2% withdrawal has a very low motivation to learn, 33% of students who have learning withdrawal by learning in the low category, 29% of orangutans who have the ability to learn in the medium category, 35% of school people have the motivation to learn in the very high category and none of the students who have the motivation to learn the category is very high. Of the four aspects of learning motivation used in data mining, the aspect of confidence is the lowest aspect of student motivation in withdrawal at SMPN 1 Sucinaraja.Keywords: Learning motivation, Withdrawal Students of SMPN 1 Sucinaraja.